Effect of surface treatments of laboratory-fabricated composites on the microtensile bond strength to a luting resin cement Efeito dos tratamentos de superfície de resinas compostas de laboratório na resistência a microtração de um agente de fixação resinoso - Carlos José Soares; Marcelo Giannini; Marcelo Tavares de Oliveira; Luis Alexandre Maffei Sartini Paulillo; Luis Roberto Marcondes Martins (University of São Paulo, 2004)
The purpose of this study was to evaluate the influence of different surface treatments on composite resin on the microtensile bond strength to a luting resin cement. Two laboratory composites for indirect restorations, Solidex and Targis, and a conventional composite, Filtek Z250, were tested. Forty-eight composite resin blocks (5.0 x 5.0 x 5.0mm) were incrementally manufactured, which were randomly divided into six groups, according to the surface treatments: 1- control, 600-grit SiC paper (C); 2- silane priming (SI); 3- sandblasting with 50 mm Al2O3 for 10s (SA); 4- etching with 10% hydrofluoric acid for 60 s (HF); 5- HF + SI; 6 - SA + SI. Composite blocks submitted to similar surface treatments were bonded together with the resin adhesive Single Bond and Rely X luting composite. A 500-g load was applied for 5 minutes and the samples were light-cured for 40s. The bonded blocks were serially sectioned into 3 slabs with 0.9mm of thickness perpendicularly to the bonded interface (n = 12). Slabs were trimmed to a dumbbell shape and tested in tension at 0.5mm/min. For all composites tested, the application of a silane primer after sandblasting provided the highest bond strength means. O objetivo deste estudo foi avaliar a influência de diferentes tratamentos de superfície na resistência de união de resinas compostas a um agente de fixação resinoso. Dois compósitos de laboratório, Solidex e Targis, e um compósito convencional, Filtek Z250, foram testados. Quarenta e oito blocos de resina composta (5.0 x 5.0 x 5.0mm) foram confeccionados através da técnica incremental, para cada compósito testado, e foram aleatoriamente divididos em 6 grupos. Os blocos foram submetidos a seis tratamentos de superfície: 1 - Controle, Lixa 600-SiC (C); 2 - Silanização (SI); 3 - Jateamento com Al2O3 50µm por 10 segundos (SA); 4 - Condicionamento com ácido fluorídrico por 60 segundos (HF); 5 - HF + SI; 6 - SA + SI. Blocos submetidos ao mesmo tratamento foram unidos com o agente de fixação resinoso Rely X. Uma carga de 500g foi aplicada por 5 minutos e as amostras foram fotoativadas por 40 segundos. Os blocos unidos foram seccionados em fatias de 0.9mm de espessura perpendicularmente à interface de união (n = 12). Foram realizadas constrições limitando a interface de união a 1mm e as amostras foram levadas para o ensaio de tração. As maiores médias de união foram obtidas para as amostras submetidas à aplicação do silano após o jateamento com Al2O3.